ANALISIS ASUHAN KEPERAWATAN DENGAN AROMATERAPI LAVENDER UNTUK MENINGKATKAN KUALITAS TIDUR PADA PASIEN HEMODIALISA - Valery Oktavia (2022)
Hemodialysis is one of the therapies for end-stage renal disease patients. However, hemodialysis therapy itself causes some side effects in the form of physical and mental symptoms. One of the side effects that hemodialysis patients often experience is difficulty sleeping and it affects their sleep quality. This study was conducted with the aim of helping hemodialysis patients improve sleep quality with lavender aromatherapy intervention. This intervention was carried out on two patients undergoing hemodialysis at Bhayangkara R. Said Sukanto Hospital. Lavender aromatherapy was given for 1 week and its effectiveness was evaluated using the Pittsburgh Sleep Quality Index (PSQI) and Visual Analog Scale (VAS) Daytime Sleepiness Level Questionnaire. The results of the evaluation showed that lavender aromatherapy was effective in improving the sleep quality of hemodialysis patients as evidenced by the PSQI Score and VAS Daytime Sleepiness Level scores in both patients decreased after being given lavender aromatherapy intervention for a week. Keywords : hemodialysis, sleep quality, lavender aromatherapy